Smart buildings digitalization. Case studies on data centers and automation - Swathika, O. V. Gnana; Karthikeyan, K.; Padmanaban, Sanjeevikumar (Boca Raton, FL : CRC Press, 2022)
"This book explains data centres concept including data collection, public parking systems, smart metering, and sanitizer dispenser. Electric urban transport systems and effective electric distribution in smart cities are discussed as well. The extensive role of power electronics in smart building applications like Electric vehicles, Rooftop terracing, and Renewable Energy Integration is included. Case Studies on automation in smart homes, commercial, and official buildings are elaborated. Describes complete implication of smart buildings via industrial, commercial and community platforms"--
1Nonlinear Controller For Electric Vehicles In Smart Buildings2Guidance System For Smart Building Using Li-Fi3Smart Building Automation System4Semi-Autonomous Human Detection, Tracking And Following Robot In A Smart Building5Current-Starved And Skewed Topologies Of CNTFET Based Ring Oscillators For Temperature Sensors6Efficient Data Storage With Tier Iv Data Centers In Smart Buildings7IoT Based Data Collection Platform For Smart Buildings8Sensor Data Validation For IoT Applications9Energy Economic Áppliances Scheduling For Smart Home Environment10IoT Based Smart Metering11Smart Energy Management System For Smart Homes12Design And Implementation Of Prototype For Smart Home Using Internet Of Things And Cloud13IoT Platform For Monitoring And Optimization Of The Public Parking System In Firebase14IoT Based Smart Health Monitoring System15Energy Management System For Smart Buildings16Augmented Lagrangian Model To Analyze The Synergies Of Electric Urban Transport Systems And Energy Distribution In Smart Cities17Grid Interconnected Photovoltaic Power System With LCL Filter workable For Roof Top Terracing18An Efficient ZCS Based Boost Converter For Commercial Building Applications19Implementation Of Smart Grid & Case Studies Through SBEMS / ETAP In Commercial & Official Buildings20Datalogger Aided Stand-Alone PV System For Rural Electrification21Smart Solar Modules For Smart Buildings22IoT Based Smart Contactless Hand Sanitizer Dispenser (Covid 19)
OCLC-licensed vendor bibliographic record.
Keywords: Intelligent buildings -- Equipment and supplies; Buildings -- Communication systems; Electronic data processing -- Equipment and supplies; Electronic data processing departments; COMPUTERS / General; COMPUTERS / Networking / General; TECHNOLOGY / Electricity